2018
DOI: 10.1038/s41598-017-18279-w
|View full text |Cite
|
Sign up to set email alerts
|

Reverse micelle Extraction of Antibiotics using an Eco-friendly Sophorolipids Biosurfactant

Abstract: Reverse micelles extraction of erythromycin and amoxicillin were carried out using the novel Sophorolipids biosurfactant. By replacing commonly used chemical surfactants with biosurfactant, reverse micelle extraction can be further improved in terms of environmental friendliness and sustainability. A central composite experimental design was used to investigate the effects of solution pH, KCl concentration, and sophorolipids concentration on the reverse micelle extraction of antibiotics. The most significant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Apart from the petroleum industry, environmental remediation, and agriculture, biosurfactants are used in other industries, such as laundry detergents, medical/pharmaceuticals, food industry, textile, paint, leather, paper, mining, nanotechnology, bioprocessing, and recently in energy-saving technology [20,25,26,38,170,171,172,173,174,175,176,177,178,179,180,181,182,183,184,185]. The multifunctionality and application versatility lies in their properties (surface and interfacial tension reducing ability, low CMC, wettability, specificity, antimicrobial activity) and their advantages (environmental friendliness, biodegradability, biocompatibility, low toxicity, ease of production, chemical diversity, and cost-effectiveness).…”
Section: Biosurfactants In Other Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the petroleum industry, environmental remediation, and agriculture, biosurfactants are used in other industries, such as laundry detergents, medical/pharmaceuticals, food industry, textile, paint, leather, paper, mining, nanotechnology, bioprocessing, and recently in energy-saving technology [20,25,26,38,170,171,172,173,174,175,176,177,178,179,180,181,182,183,184,185]. The multifunctionality and application versatility lies in their properties (surface and interfacial tension reducing ability, low CMC, wettability, specificity, antimicrobial activity) and their advantages (environmental friendliness, biodegradability, biocompatibility, low toxicity, ease of production, chemical diversity, and cost-effectiveness).…”
Section: Biosurfactants In Other Industriesmentioning
confidence: 99%
“…Similarly, Balakrishnan et al [195] used biosurfactant to optimize the synthesis of polyethylene nanoparticles. The use of biosurfactant aided a reverse micelles system to recover antibiotics, enzymes, and proteins, which [170,180] is relatively new but shows high promise, with the potential for high-scale production and continuous operation. The application of biosurfactants in energy-saving technology with respect to eco-ice systems has been less publicized.…”
Section: Biosurfactants In Other Industriesmentioning
confidence: 99%
“…It is reported that these biosurfactants have been employed broadly for various applications covering industrial and environmental fields [7][8][9]. However, few extraction methods employing biosurfactants have been reported, limited to just the biodispersive liquid microextraction based on nano rhamnolipid aggregates [10] and the reverse micelle extraction of antibiotics using sophorolipids [11]. Trehalose lipid (Supporting Information Figure S1) is one kind of biosurfactant produced by some bacteria, and it possesses various biological and physicochemical properties, such as antitumour [12], antiviral, and antimicrobial activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the petroleum industry, environmental remediation and agriculture, biosurfactants are used in other industries such as laundry detergents, medical/pharmaceuticals, food industry, textile, paint, leather, paper, mining, nanotechnology, bioprocessing, and recently in energy-saving technology [20,25,26,38,[170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185]. The multifunctionality and application versatility lies in their properties (surface and interfacial tension reducing ability, low CMC, wettability, specificity, antimicrobial activity) and their advantages (environmental friendliness, biodegradability, biocompatibility, low toxicity, ease of production, chemical diversity and cost-effectiveness).…”
Section: Biosurfactants In Other Industriesmentioning
confidence: 99%
“…Similarly, Balakrishnan et al [195] used biosurfactant to optimize the synthesis of polyethylene nanoparticles. The use of biosurfactant aided reverse micelles system to recover antibiotics, enzymes and proteins [170,180] is relatively new but shows high promise with a potential for high scale production and continuous operation. The application of biosurfactants in energy-saving technology with respect to eco-ice systems are less publicized.…”
Section: Biosurfactants In Other Industriesmentioning
confidence: 99%